Sharing rivals, sending weapons: Rivalry and cooperation in the international arms trade, 1920–1939 - Marius Mehrl; Daniel Seussler; Paul W. Thurner (The Review of International Organizations, 2023)
States must navigate the structure of the international system in their relations with other states. One crucial component of this structure are rivalries as they indicate latent threat to states. Rivalries should thus influence how states behave within the given system, but also how they seek to shape and restructure it. Focusing on arms transfers, we clarify how the systemic structure implied by rivalries drives states' efforts to engage in security cooperation with other states. Intuitively, a rivalry with another country should diminish an exporter's propensity to transfer weapons there. But what is more, we argue that rivalries outside of this focal dyad matter as a potential importer's enmity towards other countries will reveal information about its security interests to the exporter. Specifically, sharing rivalries with the same set of countries will signal to the exporter that there is a congruence in security interests and thus facilitate security cooperation. This security cooperation should take the form of arms transfers, at least if exporters value buck-passing and fear entrapment. We test our expectations using original data on Major Conventional Weapons transfers in the Interwar years, a period where this condition likely holds, and inferential network analysis models. Sharing rivals increases two countries' probability to trade arms whereas a rivalry between countries exhibits no effect. This research contributes to our understanding of security cooperation, the arms trade, and networked international relations.
Keywords: F1; F19; F5; F51; F52; N40; N70; 320; Rivalry; Arms trade; Networked international relations; Interwar period; Inferential network analysis